PENGARUH PENETAPAN HARGA, DISKON, KERAGAMAN PRODUK, KERAMAHAN, TATA RUANG, DAN TEMPAT PARKIR TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN JADI - Prayitno, Budi (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2003)
The problem in this research is price, discount, deversifrcation, shoping room, parking room, and service influece the buy decision for dress in Vida Mayen Sungkono, Rimo and Matahari Tunjungan Plasa, Matahari Surabaya plasa and Ramayana Jembatan Merah Plasa at Surabaya. The method use in this research is explanatory research,for making empiric generalization, to determine concept, to prove in developing theory where data collection and analisis go at the same time. The research population are the customers, with 100 samples wich taken in random sampless,where the datas collected were from primary datas with a spread questionary and direct interviews with the respondents and the secondair datas which have been collected from asociated institution. Variables which have observed carefully in this research is the amaunt of goods as a variable dependent and price, discount, deversifrcation, shoping room, parking room, and service as an independent variable. Datas collection were done by direct interviews with the respondent and a direct questionary to consumers in Vida Maijen Sungkono,Rimo and Matahari Tunjungan Plasa,Matahari Surabaya plasa and Ramayana Jembatan Merah Plasa at Surabaya Analisis method with cross tabulation,to sen contingency table wich shows wether there is any collection between dependent variable which cover the amount of goods and independent variable is price, discount, deversification, shoping room, parking room,and service.And chi square tess metode the different between observation and expectation frequency. From the evaluation towards the coefficient chi square calculation result, either from pearson chi square it will obtain chi square value bigger than chi square table, which means that each variable presence has an significant influence towards consumer purchasing decision.